2021
DOI: 10.1172/jci.insight.144762
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma XOR activity induced by NAFLD/NASH and its possible involvement in vascular neointimal proliferation

Abstract: Xanthine oxidoreductase (XOR) is an enzyme that catalyzes hypoxanthine to xanthine and xanthine to uric acid, respectively. However, the underlying mechanisms of increased plasma XOR and its pathological roles in systemic diseases, such as atherosclerosis, are not fully understood. In this study, we found that changes in plasma XOR activity after bariatric surgery closely associated with those in liver enzymes, but not with those in BMI. In a mouse model of nonalcoholic fatty liver disease/steatohepatitis (NAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Our previous studies in both humans and mice demonstrated that increased plasma XOR activity was directly induced by liver damage, together with increases in liver enzymes such as serum ALT and AST. Moreover, high XOR in liver disease conditions accelerated purine catabolism in the plasma per se using hypoxanthine secreted from vascular endothelial cells or adipocytes as substrate, which was accompanied by the development of vascular endothelial injury and neointimal proliferation [ 11 , 12 , 13 ]. Additionally, a cross-sectional study by another group reported a significant positive correlation between plasma XOR activity and CAVI in patients with type 2 diabetes and liver dysfunction [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies in both humans and mice demonstrated that increased plasma XOR activity was directly induced by liver damage, together with increases in liver enzymes such as serum ALT and AST. Moreover, high XOR in liver disease conditions accelerated purine catabolism in the plasma per se using hypoxanthine secreted from vascular endothelial cells or adipocytes as substrate, which was accompanied by the development of vascular endothelial injury and neointimal proliferation [ 11 , 12 , 13 ]. Additionally, a cross-sectional study by another group reported a significant positive correlation between plasma XOR activity and CAVI in patients with type 2 diabetes and liver dysfunction [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Human XOR expression is detected mainly in liver, lungs, and gut [ 11 ]. Recently, we reported that circulating XOR in humans and mice markedly increased with elevations in liver enzymes such as serum alanine aminotransferase (ALT) or aspartate aminotransferase (AST), reflecting excessive leakage of hepatic XOR, and that topiroxostat, a selective XOR inhibitor, suppressed plasma XOR activity and attenuated the development of vascular neointima formation in a diet-induced mouse model of NAFLD/NASH [ 12 , 13 ]. Therefore, we hypothesize that XOR inhibitors may have the potential to prevent or delay cardiovascular complications, especially in patients with liver dysfunction, possibly beyond their UA-lowering effect.…”
Section: Introductionmentioning
confidence: 99%
“…Higher hypoxanthine levels were associated with obesity and were secreted from adipose tissues under hypoxic conditions [ 38 , 39 ]. Increase in plasma XOR activity was induced by the disease [ 40 ]. The decrease in xanthine levels with the improvement in liver fat can be explained by the fact that ezetimibe attenuates steatohepatitis through the induction of autophagy and the inhibition of NLRP3 inflammasome [ 41 ] which would result in the downregulation of the purine catabolism pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The main role in the formation of UA is purines, and the accumulation of purines in the body is the main reason for the production of HUA. XO is the critical enzyme in the last step of UA synthesis, which catalyzes the oxidation of hypoxanthine to xanthine and then to UA, or directly to UA ( Furuhashi et al, 2018 ; Kawachi et al, 2021 ). Several studies have shown that flavonoids ( Scheepers et al, 2019 ) and saponins ( Xu et al, 2022 ) isolated from TCM can reduce UA by reducing the content of XO in the liver while enhancing renal excretion of UA.…”
Section: Discussionmentioning
confidence: 99%